Optimal distributed transaction of multiple microgrids in grid-connected and islanded modes considering unit commitment scheme. (November 2021) - Wang, Zhuo; Wang, Luhao; Li, Zhengmao; Cheng, Xingong; Li, Qiqiang
Highlights: A model convexification for multi-directional energy transactions for MMGs in two modes. A rounding-off procedure with thresholds for out-of-limit problems of generators. An AOM to solve continuous and binary variables alternately in a distributed manner. A theoretical convergence proof for AOM with rounding-off procedure. Abstract: This paper addresses multi-directional energy trading problems (ETPs) for multiple microgrids (MMGs) in grid-connected and islanded modes considering the unit commitment (UC) scheme. Firstly, a mixed integer quadratic programming (MIQP) model is formulated to describe unit commitment problems (UCPs) for each microgrid (MG) and energy transactions among MMGs. Then binary variables from UCPs are relaxed to convert the original non-convex model into a tractable convex one. Furthermore, an alternating optimization method (AOM) composed of alternating direction method of multipliers (ADMM) and MIQP block is proposed to solve continuous and binary variables alternately. Especially, a rounding-off procedure with thresholds is designed to treat out-of-limit problems of generators and smooth the parameter passing between ADMM and MIQP block with corresponding convergence proof. Finally, comprehensive comparisons are conducted to demonstrate the effectiveness of proposed method. Simulation results indicate that AOM can be directly applied to solve ETPs for MMGs in a distributed manner, and thresholds are effective for operators to adjust the operating range of generators flexibly under the condition that ETPs are completely solvable.